Liver stiffness measured by two-dimensional shear-wave elastography predicts hepatic vein pressure gradient at high values in liver transplant candidates with advanced liver cirrhosis - Frankova, Sona; Lunova, Mariia; Gottfriedova, Halima; Senkerikova, Renata; Neroldova, Magdalena; Kovac, Jozef; Kieslichova, Eva; Lanska, Vera; Urbanek, Petr; Spicak, Julius; Jirsa, Milan; Sperl, Jan (PloS one, 2021)
Liver stiffness is a reliable non-invasive predictor of Hepatic Venous Pressure Gradient (HVPG) above 10 mm Hg. However, it failed to predict higher thresholds of HVPG. Our aim was to investigate whether liver stiffness and selected previously published non-invasive blood biomarkers could predict higher HVPG thresholds in liver transplant candidates without ongoing alcohol use. One hundred and nine liver transplant candidates with liver cirrhosis of various aetiologies underwent direct HVPG measurement, liver stiffness measurement by 2D shear-wave elastography (Aixplorer Multiwave, Supersonic Imagine, France) and assessment of blood HVPG biomarkers (osteopontin, VCAM-1, IL-6, TNF-α, IL-1ra/IL-1F3 and ELF score). The correlation between liver stiffness and HVPG was linear up to 30 mm Hg of HVPG (r = 0.765, p < 0.0001). The regression lines had similar slopes for HVPG values below and above 16 mm Hg (p > 0.05) and the correlation in patients with HVPG <16 mm Hg (r = 0.456, p = 0.01) was similar to patients with HVPG ≥ 16 mm Hg (r = 0.499, p < 0.0001). The correlation was similar in the subgroup patients with alcoholic (r = 0.718, p < 0.0001), NASH (r = 0.740, p = 0.008), cryptogenic (r = 0.648, p = 0,0377), cholestatic and autoimmune (r = 0.706, p < 0.0001) and viral cirrhosis (r = 0.756, p < 0.0001). Liver stiffness distinguished patients with HVPG above 16, and 20 mm Hg with AUROCs 0.90243, and 0.86824, sensitivity 0.7656, and 0.7027, and specificity 0.9333, and 0.8750. All studied blood biomarkers correlated better with liver stiffness than with HVPG and their AUROCs did not exceed 0.8 at both HVPG thresholds. Therefore, a composite predictor superior to liver stiffness could not be established. We conclude that liver stiffness is a clinically reliable predictor of higher HVPG thresholds in non-drinking subjects with advanced liver cirrhosis.
Keywords: Liver Cirrhosis; Male; biologické markery; venae hepaticae; Biomarkers; Hepatic Veins; fibróza; Česká republika; venózní tlak; Portal Pressure; Adult; Aged; dospělí; Prospective Studies; mužské pohlaví; senioři; lineární modely; Fibrosis; pružnost; Czech Republic; Hypertension, Portal; senioři nad 80 let; elastografie; Venous Pressure; lidé; jaterní cirhóza; ženské pohlaví; játra; portální hypertenze; Humans; Sensitivity and Specificity; senzitivita a specificita; Linear Models; Aged, 80 and over; Elasticity; Elasticity Imaging Techniques; portální tlak; Liver; Female; lidé středního věku; Middle Aged; prospektivní studie